PERUBAHAN SOSIAL BUDAYA DAN EKONOMI MASYARAKAT KAMPUNG ARBOREK KABUPATEN RAJA AMPAT SETELAH MENJADI KAWASAN WISATA - Nastassja Virginia Pongantung (AGRI-SOSIOEKONOMI, 2018)
This study aims to describe the socio-cultural conditions and economic conditions of the Arborek village community of Raja Ampat Islands of West Papua following the development of tourist areas and analyzing the impact of tourism development on local communities. This study was conducted for 1 week because the location of only one small island that is Arborek village on 23-29 October 2017. This research was conducted by field study and literature study. Respondents consist of local community in arborek village. Selection of respondents as a research unit is done by purposive sampling. The selected respondents were adat leaders, community leaders and community groups. The research method used is descriptive and explorative which aims to get the facts. The results of this study indicate the impact of positive social changes such as knowledge and attitudes about the benefits of forests and coral reefs for human life as well as Increased income and employment.